Copper Oxalate Multilayer Micro-Sheet Film Grown Directly on Cu Substrate - Song, Hainan; Xu, Juncui; Wei, Yanxin (Asian Journal of Chemistry, 2012)
A kind of copper oxalate film was prepared in aqueous acid solution at room temperature. During the preparation, a copper foil was used as substrate while K2S2O8 was used as oxidizing agent. The film prepared was covered with micro-sheets which had polymer-like structure. This technique could be considered as an effective way to energy-retrenched, time-saving and environment friendly.